Weather Forecast In Medan City With Hopfield Artificial Neural Network Algorithm - Anwar, Badrul; Jalinus, Nizwardi; Abdullah, Rijal (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Many aspects are very influential for the continuity of Indonesian society, especially Medan. One of the aspects that affect the continuity of the people of Medan is the weather. Weather plays an important role in various sectors, such as agriculture, aviation, and many other sectors. The Meteorology, Climatology and Geophysics Agency (BMKG) is always trying to develop their innovations to be able to provide accurate weather information to the public. To assist the process of disseminating weather information to the public in Medan City, we need a Weather Forecast application that uses Website-based computer technology so that it can help disseminate weather information easily and effectively which is generated through the support of the Hopfield method by connecting the application with BMKG data. Based on the results of this study, a weather forecasting application was successfully built to help disseminate weather information in Medan City to all Medan City people who want to get information about the weather.